2015
DOI: 10.1007/s00345-015-1523-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric ultrasound in the detection of prostate cancer: a systematic review

Abstract: Purpose To investigate the advances and clinical results of the different ultrasound modalities and the progress in combining them into multiparametric UltraSound (mpUS).MethodsA systematic literature search on mpUS and the different ultrasound modalities included: greyscale ultrasound, computerized transrectal ultrasound, Doppler and power Doppler techniques, dynamic contrast-enhanced ultrasound and (shear wave) elastography.Results Limited research available on combining ultrasound modalities has presented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
80
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 59 publications
0
80
0
2
Order By: Relevance
“…The combination of different ultrasound modalities significantly improves diagnostic performance [16], and examination using transrectal and power Doppler ultrasound remains accessible and cheap. New modalities, such as differential tissue harmonic imaging with high-frequency probes, perform better than fundamental sonography.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The combination of different ultrasound modalities significantly improves diagnostic performance [16], and examination using transrectal and power Doppler ultrasound remains accessible and cheap. New modalities, such as differential tissue harmonic imaging with high-frequency probes, perform better than fundamental sonography.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors reported additional value of the Doppler techniques over TRUS [9,16,18]. For Eisenberg et al [22], adding PDS to TRUS improved specificity from 47 to 74 %, although the sensitivity decreased from 58 to 47 %.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the diagnosis of prostate cancer with ultrasound (US) imaging, gray scale US, Doppler US, dynamic contrast enhanced (DCE)-US and elastography have been widely used (1). The majority of prostate cancers are harder than normal prostatic tissue, due to increased micro-vascularity and a stromal response leading to increased collagen deposition around the tumor (2).…”
Section: Introductionmentioning
confidence: 99%